Еще раз о протосистеме армянского алфавита («данииловых письменах»): Удалось ли критику «закрыть» Открытие? - Муравьев, Сергей (Институт языкознания РАН)
In 1979, the French and Russian (then Soviet) scholar in classics and future caucasologist Serge Mouraviev sent to the Revue des Études arméniennes (Paris) and the Patma-Banasirakan Handes (Yerevan) two identical papers, one in French and one in Russian (each consisting of two articles), on a discovery he had made while studying the Armenian alphabet and on the non trivial information concerning the creation of this script he had drawn from this discovery. The REArm published the entire paper in its 1980 issue, PBH published only the first half of it in 1980 and inserted in 1982, instead of the second half, a critical article written by the well known Leningrad historian Karen Yuzbashyan. Mouraviev’s response to Yuzbashyan criticism was also censured. Thus an important part of the Armenian readership in the Soviet Union was deprived of any direct access to Mouraviev’s discovery (copies of RÉArm were rare in the USSR and French obviously was much less read than Russian). The discouraged scholar still managed to publish in 1985 a short popular abstract of his paper in Literaturnaja Armenija and abandonned the subject until 2009. In 2010 he published in French a book entitled Erkataguir where he developped his 1985 article with numerous additions including inter alia an Armenian palaeography of the 5th and 6th centuries and the 16 most important ancient testimonies on the creation of the alphabet by Mesrop Mashtots. But this book still remains untranslated either into Russian or into Armenian. This is why the editors of Arm’anskij Gumanitarnyj Vetsnik decided to publish or republish all Mouraviev’s Russian papers of the 1980’s on the subject, including Yuzbashyan’s criticism and Mouraviev’s response to it. As to their contents (except for the polemics), the non speakers of Russian, will find them in the aforementioned papers and book written in French.
Keywords: Армянский алфавит